COPING STRATEGIES AND ITS INFLUENCE ON THE REDUCTION OF PSYCHOLOGICAL EFFECTS EXPERIENCED BY NURSES IN HANDLING COVID-19 CASES - Nurul Azzarah; Maria Jacinta Arquisola (President University, 2021)
In facing the COVID-19 pandemic, Indonesian nurses have to work under pressure and non-stop because of the imbalance of the ratio between nurses and patients. It affects their psychological health and results in a lot of nurses feeling stressed while doing their job. This study aims to find out about the effect of coping strategies – emotion-focused coping, problem-focused coping, and escape-avoidance coping - in reducing the psychological effects experienced by Indonesian nurses in handling COVID-19 cases. A total of 110 nurses who work in special referral hospitals and treating COVID-19 patients participated in this study. Using multiple regression analysis, the study found that there is reduction in COVID-19’s psychological effect when they employ coping strategies, with the highest result being problem-focused coping supported by the presence of such medical aids as PPE (personal protective equipment), and ventilators which enable them to focus on the job better and feel assured of their own safety. This study not only finds that nurses find a way to reduce their stress but also recommend that a solution for the reduction of COVID-19 effects is for government to ensure their safety by providing and distributing personal protective equipment (PPE) evenly and thoroughly to ensure safety and reduce nurses' stress. This study contributes to understanding how Indonesian medical personnel cope with the COVID-19 effects by employing coping strategies, and adds novel empirical contribution to scant research on Indonesian medical personnel and COVID-19 effects in an Indonesian context.Keywords: Coping Strategy, Stress, Nurses, Psychological Effect, Covid-19